A high-quality genome provides insights into the new taxonomic status and genomic characteristics of Cladopus chinensis (Podostemaceae). (1st April 2020) - Xue, Ting; Zheng, Xuehai; Chen, Duo; Liang, Limin; Chen, Nan; Huang, Zhen; Fan, Wenfang; Chen, Jiannan; Cen, Wan; Chen, Shuai; Zhu, Jinmao; Chen, Binghua; et al.
Abstract: The Podostemaceae are ecologically and morphologically unusual aquatic angiosperms that survive only in rivers with pristine hydrology and high water quality and are at a relatively high risk of extinction. The taxonomic status of Podostemaceae has always been controversial. Here, we report the first high-quality genome assembly for Cladopus chinensis of Podostemaceae, obtained by incorporating Hi-C, Illumina and PacBio sequencing. We generated an 827.92 Mb genome with a contig N50 of 1.42 Mb and 27, 370 annotated protein-coding genes. The assembled genome size was close to the estimated size, and 659.42 Mb of the assembly was assigned to 29 superscaffolds (scaffold N50 21.22 Mb). A total of 59.20% repetitive sequences were identified, among which long terminal repeats (LTRs) were the most abundant class (28.97% of the genome). Genome evolution analysis suggested that the divergence time of Cladopus chinensis (106 Mya) was earlier than that of Malpighiales (82 Mya) and that this taxon diverged into an independent branch of Podestemales. A recent whole-genome duplication (WGD) event occurred 4.43 million years ago. Comparative genomic analysis revealed that the expansion and contraction of oxidative phosphorylation, photosynthesis and isoflavonoid metabolism genes in Cladopus chinensis are probably related to the genomic characteristics of this growing submerged species. Transcriptome analysis revealed that upregulated genes in the shoot group compared to the root group were enriched in the NAC gene family and transcription factors associated with shoot development and defense responses, including WUSCHEL (WUS), ASYMMETRIC LEAVES (ASL), SHOOT MERISTEMLESS (STM), NAC2, NAC8, NAC29, NAC47, NAC73, NAC83 and NAC102. These findings provide new insights into the genomic diversity of unusual aquatic angiosperms and serve as a valuable reference for the taxonomic status and unusual shoot apical meristem of Podostemaceae.